Petrophysical and Reservoir Characteristics of Sedimentary Rocks From Offshore West Baram Delta, Sarawak Basin, Malaysia - Ben-Awuah, Joel; Padmanabhan, E.; Andriamihaja, S.; Amponsah, P.; Ibrahim, Y. (Slovnaft VÚRUP, 2016)
Sedimentary successions in the Baram Delta consist mainly of alternating sandstones and siltstones with rare intercalations of mudstones. This study examines the petrophysical variations between these Middle to Upper Miocene sedimentary facies with emphasis on porosity, permeability, pore size distribution, displacement pressure and irreducible water saturation. Over 130 core samples retrieved from seven offshore wells in four fields of the West Baram Delta were analyzed using thin sections, SEM with EDX, poroperm and mercury porosimetry. Six sandstone facies were identified in the studied wells including coarse grained sandstones, very fine grained sandstones, fine grained massive sandstones, bioturbated sandstones and parallel laminated sandstones. Average porosity and permeability respectively for the sandstone facies are 24.97% and 1910.6mD for coarse grained sandstones, 5.66% and 1.4mD for very fine grained sandstones, 16.48% and 23.28mD for bioturbated sandstone, 19.75% and 113.17mD for parallel laminated sandstones, 19.85% and 100.36mD for poorly sorted fine grained massive sandstone and 24.65% and 402.14mD for moderately sorted fine grained massive sandstones. The results indicate that the coarse grained sandstones are the best in terms of reservoir rock quality compared to the very fine grained sandstones that have the worst reservoir rock characteristics. The excellent reservoir rock quality in the coarse sandstones is attributed to its lack of cement between grains, very good intergranular porosity and pore connectivity. The poor reservoir rock quality in the very fine sandstone is attributed to its high degree of consolidation, lack of pores and high amount of cement and matrix between grains. A significant reduction in porosity and permeability is observed in the bioturbated sandstones due to the concentration of clays, heavy minerals and pyrite within burrows by burrowing organisms resulting in localized reduction in porosity.